PERBEDAAN KUALITAS PERSAHABATAN PADA MAHASISWA DI KOTA PADANG DI TINJAU DARI JENIS KELAMIN - Shaquilla, Audrey; Nio, Suci Rahma (CAUSALITA : Journal of Psychology, 2023)
Friendship is a relationship in which two people spend a lot of time together, interact in a variety of situations, and provide each other with emotional support. Friendship is not always done with the same sex, but friendship can be done with individuals of different sexes. The purpose of this research is to see the quality of friendship in terms of gender. This study uses a type of comparative quantitative research. The sample consisted of 272 participants (161 women and 111 men) using a purposive sampling technique. The Friendship Quality Scale was used as a data collection method. Data analysis uses product moment correlation. The results of the hypothesis obtained the value of F = 3.741 with p = 0.00 (p <0.05), it can be concluded that H0 is rejected and Ha is accepted. These results indicate that there are significant differences in friendship quality between average friendships between men, between women, and between men and women.